Maja Miše. Gnathia and Related Hellenistic Ware on the East Adriatic Coast - van der Enden, Mark (Journal of Greek Archaeology, 2016)
Maja Miše’s book Gnahia and Related Ware on the East Adriatic Coast is a timely addition to the field of Hellenistic pottery studies and an excellent overview of the regional occurrence of this well-known ware. M. presents in her book a thorough examination of the occurrence of Gnathia pottery in the East Adriatic and particularly focusses on defining the local Issaean production of this ware. The occurrence of Gnathia pottery in the East Adriatic is contrasted by M. with the production of the Ware in Southern Italy (the Ware’s area of inception), for which she devises a typological and developmental framework, sheds new light not only on the development of Gnathia pottery in Southern Italy but also across the Adriatic. M’s book is therefore an excellent overview of Gnathia pottery, its origin and development, distribution in southern Italy and in the Adriatic and attempts to view the occurrence of this important ware within a wider socio-economic context.